(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
On the one hand, it is gratifying that not only the Internet has been created, but also that various information technologies that are developing on an international scale have a positive influence on the young generation, on the other hand, in order to protect them from various negative lessons, the educational environment encourages to strengthen. As a result of the emergence of social networks and their widespread use among young people, we can learn that they have a negative effect on young people. We are witnessing that they are poisoning the minds of young people by establishing themselves in social networks.